Interactive Role of Age and Sex of Dairy Workers on Postural Stress Caused during Milking - Chauhan, Deepali (Indian Journal of Extension Education, 2013)
Postural stress was measured by assessing time spent in different body postures, frequency of adopting various body  postures and angle of body deviations in lumber region of dairy workers during milking. Findings of study suggested that  squatting posture was adopted for the longest period of time along with standing posture as a frequently adopted posture  by all dairy workers. Further, time spent in different posture was maximum in females of the higher age group and  minimum in males of lower age group. However, frequency of adopting different posture was same for all dairy workers.  Angle of body deviation was observed with the help of flexi curve by dividing whole process of milking operation into  five parts-lifting of empty bucket (p1), placing of bucket on ground (p2), milking (p3),lifting of bucket containing milk (p4), carrying of bucket containing milk (p5). The angle of body deviation was maximum during milking operation (p3)  with maximum value in females of the higher age groups.
Keywords: Dairy workers; body postures; milking; body deviation